PENGARUH PERHATIAN WALI KELAS DAN ORANG TUA TERHADAP MOTIVASI BELAJAR SISWA KELAS IX DI MTs AL-HIDAYAH PATUMBAK - Sari, Novita; Saprijal, Saprijal; Siahaan, Hasnah (HIBRUL ULAMA, 2024)
This study is an ex post facto study and was conducted at MTs Al Hidayah Patumbak in class IX with a population of 30 students. The data for this study were taken using a questionnaire divided into 3 groups, namely groups to reveal data on student learning motivation, student learning interest, and student tutoring. Test scores are used to reveal their achievements. This study aims to determine how much student learning motivation, student learning interest and student tutoring are in class and outside the classroom in all subjects.